Attitude Towards Learning Communication Skills Among Undergraduate Medical Students of a Public University - Mehreen Nawab, Mehreen Nawab; Umer Nawab, Umer Nawab; Aashi Mughal, Aashi Mughal (Students’ Supplement of Journal of Rawalpindi Medical College, 2019)
Background: Communication skills are an essential in any field of life, but it is especially an essential skill to master in medical undergraduates. Objective: To assess the attitude of undergraduate medical students towards learning communication skills and to co-relate their attitude with gender and year of education. Methods: This descriptive cross-sectional study was carried out to assess the attitude of students studying in Rawalpindi Medical University towards learning communication skills. A total 278 students from 3rd, 4th, 5th year participated in this study. Written informed consent was taken. Communication Skill Attitude Scale (CSAS) was used as an assessment tool. Approval from ethical review board and institute research forum (IRF) was obtained. Data was entered and analysed by SPSS v. 22. Results: 80.1% participants were female while 19.1% were male. Number of students from 3rd, 4th, 5th year were 70(25.2%), 86(30.9%) and 122(43.9%) respectively. Results of the study revealed a relatively positive attitude towards learning communication skills among undergraduate medical students. There is no significant difference in attitude of male and female students towards learning communication skills. Also, there is no significant difference in attitude of 3rd, 4th, 5th year students. Conclusion: Positive communication skill learning attitude was observed among undergraduate medical students of Rawalpindi Medical University. Consequently, this positive attitude among students promises the success of communication skill programs if introduced. Key Words: Attitude, Medical Students, Communication Skills